Addendum: An examination of meaningful experiences during sport education - Ali Nasser Alshuraymi; Peter Hastie (CV Rezki Media, 2025)
This addendum provides additional statements on data availability and AI disclosure to enhance transparency and align the original article with current international publication standards. These updates do not affect the results, interpretation, or conclusions of the original publication.